The Effect of Green Human Resource Management on Green Innovation: The Mediating Role of Green Organizational Commitment in MSMEs in Samarinda City - Suyanto Suyanto; Dian Irma Aprianti; Eko Ravi Pratama; Lailatul Maghfiroh (Khazanah Sosial, 2025)
This study examines the influence of Green Human Resource Management (GHRM)—comprising green recruitment, green training, and green knowledge sharing—on green innovation in Micro, Small, and Medium Enterprises (MSMEs) in Samarinda, with green organizational commitment (GOC) as a mediating variable. This topic is particularly important since MSMEs, although vital in developing economies, often overlook ecological aspects. The research adopts a quantitative descriptive design with a sample of 100 food and beverage MSME owners in Samarinda, drawn from a population of 16,825 using Slovin’s formula. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 7.0. The results show that all three dimensions of GHRM significantly affect green innovation, with green knowledge sharing exerting the strongest impact, followed by green recruitment, while green training has a positive but weaker effect. Furthermore, GOC significantly mediates these relationships, with the strongest indirect effect found in the path from green knowledge sharing to green innovation. The overall model demonstrates strong feasibility and explanatory power (R² = 0.941 for green innovation). These findings indicate that HR practices aimed at environmental sustainability are most effective when supported by organizational commitment. Policy-wise, this research underscores the importance of embedding environmental awareness into recruitment, training, and knowledge-sharing processes at the MSME level. Practically, MSMEs are encouraged to institutionalize green values as part of their organizational culture to strengthen innovation and competitiveness. This study contributes originality by modeling how internal GHRM mechanisms influence innovation through organizational commitment, thereby extending previous theories and offering context-specific insights for MSMEs in Indonesia.